Nonpharmacological, nonsurgical treatments for freezing of gait in Parkinson's disease: A systematic review. Issue 2 (26th November 2019) - Delgado‐Alvarado, Manuel; Marano, Massimo; Santurtún, Ana; Urtiaga‐Gallano, Ainhoa; Tordesillas‐Gutierrez, Diana; Infante, Jon
Abstract: Freezing of gait is a disabling phenomenon that appears in a substantial number of Parkinson's disease (PD) patients as the disease evolves. It is considered to be one of the most relevant contributing factors to worsening of quality of life. Current pharmacological or surgical treatment options have limited efficacy. Thus, alternative nonpharmacological/nonsurgical approaches have emerged in recent years in an attempt to improve quality of life in PD. This systematic review summarizes studies of such therapies over the past 5 years. Thirty‐five studies were evaluated by use of a qualitative evaluation, while the methodological quality was assessed using validated tools. According to our results, there appear to be two broad categories of nonpharmacological therapies: those that seek a long‐lasting benefit and those that aim to achieve a transient effect to overcome the freezing of gait episode. Among the former, it is possible to differentiate between "passive" therapies, which include transcranial magnetic stimulation or transcranial direct current stimulation, and "active" therapies, which are based on different cognitive or physical training programs. Finally, "transient effect" therapies use different types of cues, such as visual, auditory, or proprioceptive stimuli, to attempt to shift the patient's habitual motor control to a goal‐directed one. In conclusion, a broad spectrum of nonpharmacological/nonsurgical approaches for freezing of gait has emerged in recent years with promising results. © 2019 International Parkinson and Movement Disorder Society